2019
DOI: 10.3892/ol.2019.10375
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of percutaneous microwave ablation for large non‑small cell lung cancer: A preliminary report

Abstract: The role of microwave ablation (MWA) in patients with non-small cell lung cancer (NSCLC) remains ill-defined. This retrospective study evaluated the oncological outcomes of CT-guided MWA in patients with large NSCLC. Kaplan-Meier analysis was used to evaluate overall survival (OS) and cancer-specific survival (CSS). The log-rank test was used to compare survival between patients with an NSCLC size greater or smaller than 4 cm. The likelihood of local tumor progression (LTP) was analyzed using a multivariable r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
27
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 36 publications
6
27
1
Order By: Relevance
“…MWA and CA have received increasing attention in recent years for treating malignancies of the lung (6,28,32). However, whether MWA or CA should be used in specific patients remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…MWA and CA have received increasing attention in recent years for treating malignancies of the lung (6,28,32). However, whether MWA or CA should be used in specific patients remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Larger tumors exhibit irregular tumor shapes, increasing the difficulty of the use of ablation applicators to optimize the entry route and completely kill the tumor cells resulting in tumor residues (25). Studies have reported that both MWA and CA have lower survival rates in patients with larger tumors compared with smaller tumor sizes (16,25,(28)(29)(30)39,40). However, the threshold tumor size used to differentiate small and large tumors varied across previous studies and depended on the maximum size of the tumor observed in each study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations